Yellow pigmy rice rat (Oligoryzomys flavescens) and hantavirus pulmonary syndrome in Uruguay - Delfraro, Adriana (2003)
Fil: Delfraro, Adriana. Facultad de Ciencias de la Universidad de la República, Montevideo; Uruguay.